Beyond Trial And Error: Hybrid Strategies And Practical Learning In The Digital Marketing Adoption By Culinary Entrepreneurs In Makassar - Isma Azis Riu (Abadi Institute, 2026)
This qualitative study investigates how culinary micro, small, and medium enterprises (MSMEs) in Makassar, Indonesia, learn, adopt, and integrate digital marketing strategies into their business operations. Drawing on an integrated theoretical framework combining the Technology Acceptance Model (TAM) and Entrepreneurial Learning theory, the study examines three distinct business segments: traditional food stalls (warung), home-based MSMEs, and small cafes. Using purposive sampling with 15–20 informants, data were collected through semi-structured in-depth interviews and participatory observation, and then analyzed thematically. Findings reveal that digital adoption is not a linear, rational decision but rather a dynamic journey driven by survival needs, pragmatic learning, and informal social networks. Key themes include experience-based digital learning, resource constraints, platform algorithm dependence, informal knowledge-sharing networks, and the emergence of hybrid marketing strategies. The study concludes with managerial implications offering practical, actionable guidance directly applicable to culinary business owners navigating the rapidly evolving digital landscape.